Further evidence for the hybrid status of the Brazilian native fern Hypolepis ×paulistana (Dennstaedtiaceae) - AGUSTINA YAÑEZ; PEDRO B. SCHWARTSBURD; GONZALO J. MARQUEZ (Anais da Academia Brasileira de Ciências, 2022)
Abstract Hypolepis ×paulistana was described in 2016 as a putative hybrid, known from a single gathering. The hybrid status of these plants was based solely on the intermediate morphology of the sporophyte, when compared to its presumed parent species. These were thought to be H. stolonifera and H. rugosula, but, H. rigescens (Kunze) T. Moore could not be explicitly ruled out either. In the present work, we tested the hybrid status of Hypolepis ×paulistana adding palynological evidence and by using chloroplast sequences to unambiguously identify the maternal progenitor of the species. We find that sporangia of Hypolepis ×paulistana contain both well-formed spores, as well as spores with morphological and developmental anomalies. The size of the regular spores and the abnormal spores suggest that H. ×paulistana is likely a diploid, and probably infertile hybrid. The ornamentation of the regular spores of H. ×paulistana is similar to that of H. stolonifera. The chloroplast sequences of H. ×paulistana are identical to those of H. stolonifera, as well as their sister position within the global phylogeny of the genus. Thus, we provide new evidence for the hybrid status of H. ×paulistana, and we corroborate the earlier finding that H. stolonifera is the maternal parent.